Building a systems framework to facilitate adaptive organizational change in state fish and wildlife agencies. Issue 2 (3rd December 2021) - Berl, Richard E. W.; Manfredo, Michael J.; Gasta, Mark; Smith, Dean; Sullivan, Leeann; Jacobson, Cynthia A.; Bishop, Chad; Camuso, Judy; Eason, Thomas; Hayes, John P.; Jacobson, Rick; Melcher, Curt; et al.
Abstract: State fish and wildlife agencies in the United States are confronted with the realities of a rapidly changing society. With declines in historical sources of revenue and the growth of diverse voices with values that differ from those emphasized by traditional policies and user groups, agencies are faced with diminishing relevancy and are encountering institutional challenges that inhibit their ability to serve the broader public. Here, in collaboration with a group of fish and wildlife agency leaders from 11 states, conservation professionals, and academics, we employ qualitative methods and concepts from systems theory to develop an integrative model of a state wildlife agency. We use this model to identify leverage points to induce transformational change toward an ideal future state: one driven by a system of shared values toward wildlife and a mission to improve quality of life for all people. Our findings point to the importance of developing interventions that will lead to changes in agency culture, systems of governance, and policy and action, and enhance the accessibility of natural resources and opportunities for diverse publics to engage with and benefit from fish and wildlife. We offer recommendations for state wildlife agencies to engage in adaptive organizational change and for university programs to support agency needs.